2001
DOI: 10.1002/pros.1114
|View full text |Cite
|
Sign up to set email alerts
|

Interferon‐alpha prevents selection of doxorubicin‐resistant undifferentiated‐androgen‐insensitive metastatic human prostate cancer cells

Abstract: Treatment with IFN-alpha and DOX should be further explored as a therapeutic strategy for androgen-insensitive prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…The findings of the current study are consistent with those of our previous studies, which showed that metastatic potential is located at the tumor periphery [31,32] . We previously demonstrated that cancer cells at the tumor periphery express metastasis-associated genes, such as EGFR and MMP-2/-9, and repress E-cadherin [31,32] , which might be triggered by CSC induction at the tumor periphery.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The findings of the current study are consistent with those of our previous studies, which showed that metastatic potential is located at the tumor periphery [31,32] . We previously demonstrated that cancer cells at the tumor periphery express metastasis-associated genes, such as EGFR and MMP-2/-9, and repress E-cadherin [31,32] , which might be triggered by CSC induction at the tumor periphery.…”
Section: Discussionsupporting
confidence: 83%
“…We previously demonstrated that cancer cells at the tumor periphery express metastasis-associated genes, such as EGFR and MMP-2/-9, and repress E-cadherin [31,32] , which might be triggered by CSC induction at the tumor periphery.…”
Section: Discussionmentioning
confidence: 99%
“…Immunoprecipitation was performed according to the method described previously (Kuniyasu et al , 2001). The lysates were pre-cleaned in lysis buffer with protein A/G agarose (Santa-Cruz) for 1 h at 4 °C and subsequently centrifuged.…”
Section: Methodsmentioning
confidence: 99%
“…WiDr cells (5 ϫ 10 5 ) treated with HMGB1/amphoterin anti-sense or sense S-ODN were grown in six-well plates coated with 1% agarose (Sigma Chemical Co.) and incubated at 37°C in 5% CO 2 . 22 After 24 hours, multicellular spheroids (300 to 500 m in diameter) were co-cultured with PMA-U937 cells, surface-labeled with PKH26 chemifluorescent dye (Zynaxis, Inc., Malvern, PA). Infiltration of labeled cells was observed at 480 nm with a fluorescence microscope.…”
Section: Spheroid Infiltration Assaymentioning
confidence: 99%